Development of Higher Order Thinking Skills (HOTS) Based Inferential Reading Module - Uyun Nafiah; Fitria, Wahyuni; Abadi, Ayuliamita (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
Nowadays, literacy is very important and critical thinking should be added in the teaching and learning. Therefore, this research is aimed at developing Higher Order Thinking Skills (HOTS) Based Inferential Reading Module which is suitable and practical for students of English Education Study Program. This was developmental research which used ADDIE model that consisted of five stages: analyze, design, develop, implement, and evaluate. Based on the result of validity test by two expert validators, it gained mean percentage 84.24% categorized as very valid in term of content eligibility, linguistics, presentation, and graphics components. Besides, based on the result of students’ practicality in terms of ease of use, efficiency of learning time and benefits, it was found percentage 81.13% categorized as very practical. It could be concluded that Higher Order Thinking Skills (HOTS) Based Inferential Reading Module is suitable, practical, and beneficial for the students of English Education Study Program UIN Sulthan Thaha Saifuddin Jambi.